2015
DOI: 10.1016/j.envint.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure pathways to organophosphate triesters — A biomonitoring study of mother–child pairs

Abstract: The worldwide ban of several formulations of brominated flame retardants has caused an increase in the production of organophosphorus flame retardants (PFRs) to meet the existing fire regulations for a wide range of household products. This biomonitoring study surveys the occurrence of the metabolites from PFRs and related plasticizers (dialkyl and diaryl phosphates; DAPs) in urine from a Norwegian mother-child cohort (48 mothers and 54 children). Concentrations of DAPs were higher in the children than in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
111
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(132 citation statements)
references
References 33 publications
17
111
4
Order By: Relevance
“…54% and 41%, respectively) in Oslo, Norway. Cequier et al (2015) subsequently concluded the household inhalation was a more important absorption pathway of OPFRs than through the diet for motherchild pairs in Norway. But more biomonitoring studies are needed to further discuss the contribution of various absorption pathways of OPFRs for human.…”
Section: Absorption Routes In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…54% and 41%, respectively) in Oslo, Norway. Cequier et al (2015) subsequently concluded the household inhalation was a more important absorption pathway of OPFRs than through the diet for motherchild pairs in Norway. But more biomonitoring studies are needed to further discuss the contribution of various absorption pathways of OPFRs for human.…”
Section: Absorption Routes In Humansmentioning
confidence: 99%
“…Recently, quantified DAPs and MAPs in urine have been identified as biomarkers to assess human exposure. In total, DAPs of BDCIPP, BCIPP, BCEP, BBOEP, DBP, DPHP, DEHP and some MAPs of MEHP, MBP, MCIPP, MBOEP and MPHP have been quantified in human urine, with median concentrations in the ng ml À1 range (Butt et al, 2014;Cequier et al, 2014bCequier et al, , 2015Chu et al, 2011;Cooper et al, 2011;Dodson et al, 2014;Fromme et al, 2014;Hoffman et al, 2015;Meeker et al, 2013a,b;Moller et al, 2004;Petropoulou et al, 2016;Reemtsma et al, 2011;Schindler et al, 2009a,b;Van den Eede et al, 2015b;Van den Eede et al, 2013b) (SI Table S2). However, no information is available for DAPs and MAPs or other OPFR metabolites from internal exposure studies of wild animals.…”
Section: Internal Exposurementioning
confidence: 99%
“…The reports associated with human exposure have demonstrated the reduction of sperm counts and hormone levels due to the exposure to TPhP and TDCP (Meeker and Stapleton, 2010). TCEP and TDCP are considered as carcinogens and potential neurotoxicants (Cequier et al, 2015;Salamova et al, 2014a), and may cause acute or chronic adverse effects to aquatic organisms (Cristale et al, 2013a;Kim et al, 2011). TCPP is also a suspected carcinogen (Reemtsma et al, 2008), and TnBP has neurotoxic properties after chronic exposure (Reemtsma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, OPEs are already ubiquitous in various environments, as they have been detected in sewage treatment plants (STPs) [3], indoor environments [4,5], atmospheric particles [6,7], aquatic environment [2,[7][8][9], biota [10,11] and also human body fluid [10,12]. Moreover, some halogenated OPEs, such as tris(2-chloroethyl)phosphate (TCEP), tris(chloroisopropyl)phosphate (TCPP) and tris(1,3-dichloro-2-propyl)phosphate (TDCP), are quite recalcitrant to naturally degradation or biodegradation [1,3], suggesting that they are likely to enter the aquatic environment and persistent in environment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some halogenated OPEs, such as tris(2-chloroethyl)phosphate (TCEP), tris(chloroisopropyl)phosphate (TCPP) and tris(1,3-dichloro-2-propyl)phosphate (TDCP), are quite recalcitrant to naturally degradation or biodegradation [1,3], suggesting that they are likely to enter the aquatic environment and persistent in environment. In addition, extensive studies have showed that exposure to several OPEs pose a potential health risk for animals and humans [12][13][14].…”
Section: Introductionmentioning
confidence: 99%